COVID-19 and global food security - Swinnen, Johan; McDermott, John (International Food Policy Research Institute, 2020)
The coronavirus pandemic has sparked not only a health crisis but also an economic crisis, which together pose a serious threat to food security, particularly in poorer countries. COVID-19 & Global Food Security brings together a groundbreaking series of IFPRI blog posts looking at the impacts of COVID-19 and the policy responses. IFPRI researchers and guest bloggers provide key insights and analysis on how the global pandemic is affecting global poverty and food security and nutrition, food trade and supply chains, gender, employment, and a variety of policy interventions, as well as reflections on how we can use these lessons to better prepare for future pandemics. These pieces draw on a combination of conceptual arguments, global and country-level simulation models, in-country surveys, case studies, and expert opinions. Together, they present a comprehensive picture of the current and potential impact of COVID-19 and the world’s policy responses on global food and nutrition security.